Analisis Pengaruh AI dalam Mendorong Keputusan Penggunaan PayLater melalui Personalisasi Rekomendasi E-Commerce - Ardine Ariella Hassya; Debi Irawan; Fadhlanrashif Ibrahim Supriyana; Athia Saelan; Arief Hertadi Rustam (Pusat Riset dan Inovasi Nasional, 2026)
In recent years digital technologies have begun to change consumer behavior, including the use of digital financial services like PayLater. The research aims to analyze the impact of AI-powered personalized recommendation systems on user decision-making on the PayLater option, with User Experience (UX) serving as a mediator in the process. This research adopts a quantitative approach using the PLS-SEM methodology. The research used primary data collected through a convenience questionnaire directed to Indonesian e-commerce customers who have used the PayLater feature. The findings of the research show that Artificial Intelligence (AI) personalization positively and significantly influences User Experience as well as the decision to use PayLater. In addition, User Experience partially mediates the impact of Artificial Intelligence (AI) personalization on the decision to use PayLater, thus strengthening the initial relationship. The good scope of the research model in explaining and influencing the dependent variable is indicated by the R² value. Recommendations include the need to strengthen the Artificial Intelligence (AI) powered system to I mprove User Experience and foster the use of formal digital financial services.